2022
DOI: 10.1002/adma.202106204
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic Benzenehexathiolato Coordination Nanosheets: Periodic Structure Improves Crystallinity and Electrical Conductivity

Abstract: Coordination nanosheets are an emerging class of 2D, bottom‐up materials having fully π‐conjugated, planar, graphite‐like structures with high electrical conductivities. Since their discovery, great effort has been devoted to expand the variety of coordination nanosheets; however, in most cases, their low crystallinity in thick films hampers practical device applications. In this study, mixtures of nickel and copper ions are employed to fabricate benzenehexathiolato (BHT)‐based coordination nanosheet films, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 46 publications
(27 reference statements)
1
39
0
Order By: Relevance
“…Moreover, we found that the coexistence of CoO x , an O 2 evolution cocatalyst, ,, could further enhance the photocatalytic activity for overall water splitting by NiBHT/SrTiO 3 :Al. The dual cocatalyst strategy with H 2 and O 2 evolution cocatalysts, such as RuO 2 /NiO, Pt/Co 3 O 4 , and CoOOH/RhCrO x , has been used widely to improve the photocatalytic activity for water splitting. ,, CoO x was first deposited onto SrTiO 3 :Al (denoted as CoO x /SrTiO 3 :Al) by the photodeposition method, which was combined with NiBHT by the impregnation method (denoted as NiBHT/CoO x /SrTiO 3 :Al). The gas production rates of CoO x /SrTiO 3 :Al were inferior to NiBHT/SrTiO 3 :Al (Figure f), while NiBHT/CoO x /SrTiO 3 :Al (1 wt % NiBHT and 0.5 wt % CoO x as Co ions) boasted a 4-fold increase in water splitting activity over NiBHT/SrTiO 3 :Al.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Moreover, we found that the coexistence of CoO x , an O 2 evolution cocatalyst, ,, could further enhance the photocatalytic activity for overall water splitting by NiBHT/SrTiO 3 :Al. The dual cocatalyst strategy with H 2 and O 2 evolution cocatalysts, such as RuO 2 /NiO, Pt/Co 3 O 4 , and CoOOH/RhCrO x , has been used widely to improve the photocatalytic activity for water splitting. ,, CoO x was first deposited onto SrTiO 3 :Al (denoted as CoO x /SrTiO 3 :Al) by the photodeposition method, which was combined with NiBHT by the impregnation method (denoted as NiBHT/CoO x /SrTiO 3 :Al). The gas production rates of CoO x /SrTiO 3 :Al were inferior to NiBHT/SrTiO 3 :Al (Figure f), while NiBHT/CoO x /SrTiO 3 :Al (1 wt % NiBHT and 0.5 wt % CoO x as Co ions) boasted a 4-fold increase in water splitting activity over NiBHT/SrTiO 3 :Al.…”
Section: Resultsmentioning
confidence: 85%
“…From these results, we concluded that NiBHT functioned stably as a H 2 evolution cocatalyst in the photocatalytic water splitting reaction. Moreover, we found that the coexistence of CoO x , an O 2 evolution cocatalyst, 5,27,36 could further enhance the photocatalytic activity for overall water splitting by NiBHT/ SrTiO 3 :Al. The dual cocatalyst strategy with H 2 and O 2 evolution cocatalysts, such as RuO 2 /NiO, Pt/Co 3 O 4 , and CoOOH/RhCrO x , has been used widely to improve the photocatalytic activity for water splitting.…”
Section: ■ Experimental Sectionmentioning
confidence: 87%
See 3 more Smart Citations